The Cambridge handbook of cyber behavior, Volume I, Volume II - Yan, Zheng 1958- (Cambridge University Press, 2023)
Human behavior in cyber space is extremely complex. Change is the only constant as technologies and social contexts evolve rapidly. This leads to new behaviors in cybersecurity, Facebook use, smartphone habits, social networking, and many more. Scientific research in this area is becoming an established field and has already generated a broad range of social impacts. Alongside the four key elements (users, technologies, activities, and effects), the text covers cyber law, business, health, governance, education, and many other fields. Written by international scholars from a wide range of disciplines, this handbook brings all these aspects together in a clear, user-friendly format. After introducing the history and development of the field, each chapter synthesizes the most recent advances in key topics, highlights leading scholars and their major achievements, and identifies core future directions. It is the ideal overview of the field for researchers, scholars, and students alike